Optimization of the internal structure and shape of a 470 dinghy centerboard - Ekström, D.; Forkman, M.; Fagerström, M.; Persson, A.; Larsson, L.; Finnsgård, C. (Proceedings, 2020)
The purpose of this paper is to design an improved centerboard for the Olympic 470 sailing dinghy sailing upwind. The design is improved by introducing a composite design that makes the centerboard twist to windward when sailing upwind, thereby reducing the angle of attack of the hull. The results show that a beneficial twist up to 1.5° is possible to achieve without compromising the centerboard strength. According to our estimates, by utilizing the improved design it is possible to obtain a gain of up to 9 s per race in a world cup race.